Identifikasi Bahaya, Penilaian Risiko dan Upaya Pengendaliannya: Studi Kasus di Departemen Warehouse PT. XYZ - Jennavita Elvira; Kriswanto Widiawan (Jurnal Titra, 2023)
PT. XYZ is a company engaged in the field involved in domestic sea freightexpeditions. This Final Project used observation and interview methods with workers. The purpose of this final project is to help company to know the potential hazards of existing activities, assess the potential hazards, and determine how to reduce or eliminate these potential hazards. Analytics result s found that the PT.XYZ had five activitied with the highest risk had classified as moderate, significant, and high. Therefore, the researcher then formulated several proposals that will be dominating by administrative engineering and PPE methods. This proposal has been acknowledge and accepted by the company. The impact of implementing the proposal is predicted that the risk rating for activities before will become a low category.